A faith of our own : second-generation spirituality in Korean American churches - Kim, Sharon, 1969- (Rutgers University Press, 2010)
Second-generation Korean Americans, demonstrating an unparalleled entrepreneurial fervor, are establishing new churches with a goal of shaping the future of American Christianity. A Faith of Our Own investigates the development and growth of these houses of worship, a recent and rapidly increasing phenomenon in major cities throughout the United States. Immigration historians have depicted the second-generation as a transitional generation--on the steady march toward the inevitable decline of ethnic identity and allegiance. Sharon Kim suggests an alternative path. By harnessing religion and inno.